AN EXPLORATION OF CULTURAL ELEMENTS AND VALUES IN KOREAN STORYBOOKS: SEMIOTIC ANALYSIS - Gita Wigati; Risa Triarisanti; Ashanti Widyana (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
This research explored how cultural elements and values are represented in Korean storybooks for Korean language learners. The objectives of this study are to: 1. Identify Korean and non-Korean cultural elements depicted in Korean language storybooks for Korean language learners; 2. Identify Korean and non-Korean cultural values depicted in Korean language storybooks for Korean language learners. The analysis was conducted using Roland Barthes' semiotic approach. Based on the analysis results, 62 cultural elements and 50 cultural values were found for Korean culture. Meanwhile, for non-Korean culture, 35 cultural elements and 51 cultural values were found. The first finding related to Korean culture was its cultural elements, namely 6 cultural categories, including: monuments; groups of buildings; sites; social practices, rituals, and celebrations; knowledge and practices about nature and the universe; and traditional craftsmanship. Related to cultural values, 5 categories were found, including: time; human relations with nature; human relations with each other; behavioral motives; and human nature. The first findings related to non-Korean culture were cultural elements, namely 5 cultural categories, including: monuments; groups of buildings; sites; knowledge and practices about nature and the universe; and traditional craftsmanship. Regarding cultural values, five categories were identified as the same category found in Korean culture. Based on these findings, it can be seen that despite the author being a foreigner and not a native Korean speaker, Korean culture is still prominently featured in the book Short Stories in Korean for Intermediate Learners. The novelty in this study compared to previous studies are: 1. There is a combination of cultural elements and cultural values that create a more in-depth analysis; 2. The use of storybooks with authors who are not native speakers; 3. There is an analysis of elements that are explained more specifically.